2019
DOI: 10.1016/j.echo.2019.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Volumes and Phasic Function in Healthy Children: Reference Values Using Real-Time Three-Dimensional Echocardiography

Abstract: Background: Evaluation of left atrial (LA) size and function is important in congenital and acquired pediatric cardiac disease. Real-time three-dimensional echocardiography (3DE) offers noninvasive assessment of cardiac volumes and phasic function independent of geometric assumptions. The aim of this prospective multicenter study was to establish pediatric reference values for LA 3DE volumes and phasic function based on a large cohort of healthy children. Methods: LA data sets of 432 subjects (0 days-222 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The marker for the apex was set at the roof of the LA, and the three‐dimensional (3D) dataset was rotated 60° counterclockwise according to the recommendations of the software developer. This way the shape of the LA better resembled the respective shape of the LV in the three apical views, facilitating automated border detection and tracing 9 . Care was taken to ensure that the entire left atrium was included within a pyramidal 3D dataset.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The marker for the apex was set at the roof of the LA, and the three‐dimensional (3D) dataset was rotated 60° counterclockwise according to the recommendations of the software developer. This way the shape of the LA better resembled the respective shape of the LV in the three apical views, facilitating automated border detection and tracing 9 . Care was taken to ensure that the entire left atrium was included within a pyramidal 3D dataset.…”
Section: Methodsmentioning
confidence: 99%
“…But 2DE is subject to errors due to poor endocardial definition, narrow echocardiographic windows, and assumptions about LA shape foreshortening 6,7 . As shown in adults and children who have not undergone cardiac surgery, real time three‐dimensional echocardiography (RT‐3DE) offers an assessment of LAV independent of geometric assumptions and correlates better with CMR 8,9 . Nevertheless, no study confirms whether the criteria can be applied to assess the LAV of heart transplant patients.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Three-dimensional volumetric echocardiography (3DE) is an emerging alternative to two-dimensional echocardiography (2DE) which makes fewer geometric assumptions regarding chamber shapes and may provide benefits in accuracy and reproducibility compared to 2DE. [6][7][8] It is therefore important to establish that commercially available algorithms for 3D measurement of cardiac chambers produce comparable results. Both TomTec 4D LV-Analysis software and Philips QLAB LV 3D underestimate LV volumes compared to MRI and have relatively wide inter-vendor limits of agreement in neonates and infants.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate and reproducible measurements of cardiac chambers are a vital component of diagnosis, prognostication, medical management, and surgical referral in congenital as well as acquired heart diseases in children 1–5 . Three‐dimensional volumetric echocardiography (3DE) is an emerging alternative to two‐dimensional echocardiography (2DE) which makes fewer geometric assumptions regarding chamber shapes and may provide benefits in accuracy and reproducibility compared to 2DE 6–8 …”
Section: Introductionmentioning
confidence: 99%
“…However, the measured value of 2DE may be affected by the significant geometric assumptions that exist about LA nonsymmetrical shape or foreshortening of LA cavity in the apical views. Real-time three-dimensional echocardiography (RT3DE) is a useful tool for assessing LA volume and function, with good feasibility and reproducibility, and it has been reported that the LA measurements by RT3DE are more strongly associated with cardiac magnetic resonance imaging than those by 2DE [10,11].…”
Section: Introductionmentioning
confidence: 99%